Migrant integration: Insights from Belgium, Italy, Spain and Germany - Christina Boll; Andreas Lagemann; Achim Welsch; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2020)
Several EU Member States have traditionally been a destination for migrants, whether they come from within the EU or elsewhere in the world. The flow of migrants has led to a range of new skills and talents being introduced into local labour markets while also increasing cultural diversity. The relevance of a stronger integration of migrants into the labour markets and societal lives of host countries exists from both a macroe-conomic and an individual perspective.
Keywords: 330; Migranten; Soziale Integration; Arbeitsmarktintegration; Vergleich; Belgien; Italien; Spanien; Deutschland